Analisis Sentimen untuk Mengetahui Kelemahan dan Kelebihan Pesaing Bisnis Rumah Makan Berdasarkan Komentar Positif dan Negatif di Instagram - Flores, Veronica Ambassador; Jasa, Lie; Linawati, Linawati (Majalah Ilmiah Teknologi Elektro, 2020)
Abstract— Formulating a marketing strategy for a pioneering or long-running restaurant business is a very important thing. Analyze the weaknesses or strengths of business competitors is one of these strategies. Identification of weaknesses and strengths can be done by taking data from comments on competitors' Instagram accounts using Text Preprocessing Techniques. Text Preprocessing is a text processing algorithm, consisting of Transform Cases, Stopword Filters, Tokenize Filters, and Stemming. Instagram is one of the most widely used social media accounts as a promotional media in Indonesia. Another method that can be used is Full Text Search, this method can analyze the patterns in comments that have been parsed for classified into positive, negative, or neutral sentiment categories. This study concludes that this sentiment analysis system can automatically recognized weaknesses (based on negative comments) and strengths (based on positive comments) based on comments on Instagram accounts owned by restaurant business competitors with an accuracy of 85% and a precision value of 79%.